2006
DOI: 10.13031/2013.20411
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Long-Term Water Quality Impact of Structural BMPS

Abstract: ABSTRACT. Structural best management practices (BMPsest management practices (BMPs) are routinely used to reduce nonpoint-source pollution resulting from agricultural activities and improve water quality. Studies have demonstrated how structural management practices can improve water quality, but the duration of their effectiveness and performance is largely unknown. Although a "design life" has been established by the USDA Natural Resources Conservation Service for most structural BMPs (e.g., USDA-NRCS, 2004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(180 citation statements)
references
References 8 publications
4
174
0
2
Order By: Relevance
“…The SWAT is an effective tool for evaluating the long-term impacts of management on hydrologic processes of diverse watershed systems [12,13,38,39]. In addition, this model also estimates the climate change impacts on plant growth, stream flow, and other responses such as total water yield, ET, snowmelt, and many others by taking into account the effects of increased atmospheric CO 2 concentrations on plant development and transpiration [40,41].…”
Section: Swat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The SWAT is an effective tool for evaluating the long-term impacts of management on hydrologic processes of diverse watershed systems [12,13,38,39]. In addition, this model also estimates the climate change impacts on plant growth, stream flow, and other responses such as total water yield, ET, snowmelt, and many others by taking into account the effects of increased atmospheric CO 2 concentrations on plant development and transpiration [40,41].…”
Section: Swat Modelmentioning
confidence: 99%
“…SWAT model has been extensively used across the globe for assessing the long-term management [11], land use and climate change [1,[12][13][14][15][16] impacts on water quantity and quality at watershed scales. The development of SWAT is a continuation of United States Department of Agriculture-Agricultural Research Service (USDA-ARS) modeling experience that spans a period of over 30 years [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…SWAT application for assessing LUCC impacts on sustainable development and watershed hydrological status is gaining momentum worldwide due to enormous anthropogenic activities on the natural systems of river basins [25][26][27][28][29][30][31][32]. In a case study at the Little Miami Watershed, USA, it was recognized that there is significant reduction in flow, sediments, and nutrients were detected as the land use in the watershed shifts from predominantly agricultural to mixed rural and residential lands [33].…”
Section: Impact Analysis Of Lucc By Swat Modelmentioning
confidence: 99%
“…Large sediment reductions could be obtained, depending on the choice of Best Management Practice as indicated by [46] on their analysis of Best Management Practices for the Walnut Creek and Buck Creek watersheds in Iowa. The impacts of Best Management Practices of three 25-year SWAT scenario simulations for two small watersheds in Indiana, USA, were studied [28], and indicated that for streamflow, sediment, and total phosphate Best Management Practices in varying conditions, and best management practices in good conditions are reported. [47] reported that within the 3000 km 2 Delaware River basin in northeast Kansas, USA in response to simulated shifts of cropland into switch grass production large nutrient and sediment loss reductions are occurred.…”
Section: Impact Analysis Of Lucc By Swat Modelmentioning
confidence: 99%
“…[30] Conservation practices were modeled based on the approaches used by Bracmort et al [2006] and Arabi et al [2007]. These studies give a detailed procedure to successfully model different conservation practices in a watershed using the SWAT model.…”
Section: Conservation Practicesmentioning
confidence: 99%